Bandung Rangki Traditional House Storytelling in Cultural Heritage Tourism of Pedawa Village - Made Sera Septiani; Ni Wayan Gita Sadhana Savitri (Pubfine Media Group, 2026)
Introduction: Pedawa Tourism Village in Buleleng Regency is a Bali Aga village that preserves a rich cultural heritage. One of its most significant cultural assets is the Bandung Rangki Traditional House, which embodies architectural, spiritual, social, and philosophical values of the Bali Aga community and has the potential to be developed as a cultural heritage tourism attraction. Methods: This study employed a qualitative research approach. Data were collected through direct observation, in-depth interviews with traditional house owners, and literature review. Data analysis was conducted using qualitative techniques, including data reduction, data presentation, and conclusion drawing. Results: The findings reveal that the Bandung Rangki Traditional House represents strong local wisdom reflected in its architectural form, spatial layout based on the hulu–teben concept, and multifunctional interior integrating residential, domestic, and sacred functions. Storytelling analysis using the 5W+1H approach highlights narratives related to historical origins, social structure, cultural traditions, and moral, religious, educational, and ethical values. These narratives enhance visitors’ understanding of the house as a living cultural heritage. Conclusion: The study concludes that storytelling plays a crucial role in strengthening the cultural meaning of the Bandung Rangki Traditional House and enhancing its attractiveness as a sustainable cultural heritage tourism asset. Integrating storytelling into heritage interpretation supports the development of Pedawa Tourism Village as a culturally based and sustainable tourism destination.